Investigation of the Optimal Interval for Staged Total Knee Arthroplasty for the Treatment of Advanced Bilateral Gonarthrosis - Yilmaz, B; Sirin, E; Kilinc, B. E; Ozdemir, G; Komur, B; Heybeli, N (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2020)
PURPOSE OF THE STUDY This study investigated whether there was an optimal interval between two operations for total knee arthroplasties in patients with advanced bilateral gonarthrosis scheduled to undergo staged total knee arthroplasty (TKA). MATERIAL AND METHODS A prospective cohort of 219 patients (136 females, 83 males) undergoing staged total knee arthroplasty for the treatment of advanced bilateral gonarthrosis were followed for up to 12 months. The mean was 69.51±5.02 (56-80) years. Patients were categorized into five groups based on the time between the first and second operations; Group I (21-90 days), Group II (91-180 days), Group III (181-270 days), Group IV (271-360 days), and Group V (more than 360 days). Patients were evaluated based on time from surgery and were assigned to corresponding groups. The data recorded included age, body mass index (BMI), side of operated knee, complications, and radiological and clinical findings. Visual analog scale (VAS) for non-operated knees was applied. Activities of Daily Living Score (ADLS) was applied to the patients at last follow-up. RESULTS No statistically significant difference was noted in BMI values (p=0.634), range of joint motion (RJM) (p=0.940) and age (p=0.785) distribution between the five groups. In Group I, the mean VAS score increased by 7.83 to 7.98, 7.86 to 8.53 in Group II, by 7.85 to 8.54 in Group III, 7.85 to 8.59 in Group IV, and 7.88 to 8.64 in Group V. There was no statistically significant difference in preoperative ADLS between the groups (p=0.064), but there was a statistically significant difference in postoperative ADLS (p=0.001). Group I patients had significantly lower postoperative ADLS compared to the other groups (p=0.001). The mean increase in postoperative ADLS versus preoperative scores of all groups were statistically significant The most significant improvements occurred in Groups II and III. Similarly, preexisting pain in the non-operated knee started to increase in Group II and continued in all groups. DISCUSSION Given all these findings, we believe that it is reasonable to advise patients to receive their second TKA, 3-6 months after their initial TKA, as this interval will allow for the greatest improvements in functional and daily living activities, and pain in the non-operated knee simultaneously becomes more severe. This recommended interval would minimize both the functional problems with the operated extremity due to pain, and deformity and dysfunction in the non-operated knee and the subsequent overloading. CONCLUSIONS Even though a number of factors influence the optimal interval for staged TKAs in bilateral gonarthrosis, an interval of 91-270 days appears to be the optimal interval between surgeries in terms of minimizing pain and maximizing ADL s and knee scores. Key words: bilateral total knee arthroplasty, optimal interval, knee society scores, activities of daily living.
Keywords: kolenní kloub; Arthroplasty, Replacement, Knee; totální endoprotéza kolene; Humans; Female; Range of Motion, Articular; Prospective Studies; výsledek terapie; lidé; Knee Joint; ženské pohlaví; Male; Osteoarthritis, Knee; Treatment Outcome; rozsah kloubních pohybů; mužské pohlaví; prospektivní studie; artróza kolenních kloubů; Activities of Daily Living; činnosti denního života